Effects of low-level laser therapy on orthodontic tooth movement: Evaluation of bone density changes via 3DCBCT (Bangladesh Journal of Medical Science, 2025)
Objective Orthodontic treatment is known to cause tooth movement that is turn results in alteration in periodontal tissues including bone resorption. The impact will be enhanced with the extended length of orthodontic treatment. Hence, the attempts are made to device an approach that can minimize the loss of periodontal tissue and promote bone regeneration. When it comes to orthodontic tooth movement (OTM), previous studies using Low- Level Laser Therapy (LLLT) have produced contradictory outcomes. This research uses cone beam computed tomography (3DCBCT) to compare bone density changes before and after orthodontic treatment in an effort to determine the effect of low-level laser therapy. Research Tools and Procedures Group A, the experimental group, had LLLT after orthodontic treatment at each appointment. Each application of diode laser had an overall energy was 75 J/tooth that was applied at five different locations for 3 seconds in the buccal /palatal region of maxillary quadrant. On the other hand, control group (Group B) received only conventional orthodontics treatment. With the 3DCBCT, the gray values were measured for the interdental region (apical third) of the maxillary teeth ranging from right molar to left molar for both study groups before and after the intervention (LLLT). The gray values were presented in mean and standard deviation. The intergroup and intragroup comparisons were made with unpaired and paired t test using SPSS v22. Results and Discussion In both the experimental and control groups, there was a non-significant (P>0.05) change between the pre- and post-laser intervention grey values representing bone density in the upper right quadrant (URQ), upper midline (UM), and upper left quadrant (ULQ). Similarly, when comparing the two groups within themselves, there was no statistically significant difference (P>0.05) in the grey values. Conclusion Taking into account the study’s limitations, the results propose that LLLT does not significantly affect the changes in bone density associated with orthodontic tooth movement. Further investigation is necessary to determine the precise function of low-level laser therapy (LLLT) in tissue regeneration and its possible implications for clinical practice.BJMS, Volume: 24. Supplementary Issue 2025, Page : 133-143